Optimal Type Selection and Simulation Analysis of 0T3R Parallel Mechanism based on the Motion Characteristic of Ankle - Shaoshuai Li; Yufeng Luo; Zhixin Shi; Dongfu Xie; Zhenkun Liu (Jixie chuandong)
According to the physiological characteristics of human ankle and parallel mechanism， several 0T3R parallel mechanisms are synthesized based on the Position and Orientation Characteristics （POC） set by taking the Single-Opened Chain （SOC） as the unit. Then combined with the characteristics of human ankle， one of the 0T3R parallel mechanisms is selected， and its kinematics analysis is carried out. Based on the established inverse displacement solution equation and by using the Matlab， the data solving is carried out. Finally， the obtained data is used as the driving function to simulate the mechanism in Adams. The simulation results verify the feasibility of the parallel mechanism， and a theoretical basis for the subsequent optimization design of mechanism size is provided.